Pênfigo foliáceo em um gato de oito meses de idade: possível reação cutânea adversa a fármacos? - Lupion, Camila Gottlieb; Pino, Eloisa Helena Moreira; da Silveira., Elissandra; Stefanello, Carine Ribas; Baretta, Leticia Talita; Gerardi, Daniel Guimarães (Acta Scientiae Veterinariae, 2017)
Background: Pemphigus foliaceus is an autoimmune skin disease whose the occurrence in feline clinic is uncommom. The etiology is unknown in most cases. Althought it is a rare condition in cats, pemphigus foliaceus can be induced by drugs. It may affect both adult and old cats with no sexual or racial predilection and diagnosis is based on animal historical, clinical examination and skin histopathology. Moreover, the treatment consists in immunosuppressive-based drugs. This paper describes a pemphigus foliaceus case in an eight-month-old kitten, probably due a cutaneous adverse drug reaction. Case: A 8-month-old, neutered male mongrel cat with crusted lesions located on face was examinated at the Veterinary Hospital. The owners reported that they had adopted the patient two months before the clinical presentation suggesting that this background was unknown. The cat was treated in a local veterinary clinic with antibiotics and anti-inflammatory for rhinotracheitis and herpetic dermatitis on face due to the occurrence of sneezing and crusted pruriginous dermatitis. The kitten presented erosions, purulent exudation and crusts on pinnae, nasal and supra ocular areas, paronychia with purulent exudate and alopecia at distal portion of the tail. Supplementary exams such as skin scraping, cytology and fungal culture were performed to rule out other agents and confirm the diagnosis. The parasitological and fungal examination resulted negative despite the fact that cytological exam showed coccoid bacteria. Complete blood count and biochemical profile showed no alteration and the test for feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) resulted negative. Histological changes were consistent with intra-epidermal pustular subcorneal with acantholysis dermatitis. An immunosuppressive dose of prednisolona was prescribed for 15 days. After this time, the crusted lesions were substituted by alopecia areas. Every 20 days the corticosteroid dose was reduced by half and after 90 days, the patient showed repilation in all regions previously affected during 545 days whithout treatment. Discussion: Pemphigus foliaceus is usually an idiopathic disease but in some cases it may be induced by drugs and infectious or parasitic agents. Previous reports described that animals younger than 1 year-old and older than 17 year-old can be affected. However, the disease occurrence is rare in young cats. The age of onset of symptoms was early considering that the literature describes 5 years of age as an average for the starting of the disease. Pemphigus foliaceus is considered a pustular disease. However, pustule is rarely reported in cats in contrast with crusted lesions which are the most common clinical sign. The body regions affected were the same as reported in the literature with the addition of systemic signs as anorexia and lethargy. Fungal culture and parasitological examination should always be performed in cats with clinical evidence to discharge other agents. Diagnosis is made by skin histopathology in which acantholytic cells are the main characteristic. The importance of the differential diagnosis and skin biopsy regardless of age enabled the diagnosis and therapeutic success. It is suggested that Pemphigus foliaceus was of pharmacodermic etiology because of the age of the patient, a history of administration of unknown antimicrobial medication and the lack of recurrence of clinical manifestations after 545 days of the end of glucocorticoid treatment